CONVERSATIONAL IMPLICATURE IN A MOVIE ENTITLED JUMANJI: WELCOME TO THE JUNGLE - Aji Saputro, Moses Febriant (LITERA : Jurnal Bahasa Dan Sastra, 2021)
ABSTRACTCommunication is an action of giving and receiving information that occur betweentwo or more people. In a conversation, people tend to say more than what they want to say.Conversational implicature usually occur in daily conversation and movies as well. This studyis focused to determine the types of conversational implicature according to Grice (1975) andto determine the connotative meaning of the utterance by using a theory of Leech (1983). Theprimary data source of this study was taken from the movie itself on Netflix. The written data,the script of the movie, taken from a website. The method of collecting the data is note taking.The data from the movie is observed by watching the movie entitled Jumanji: Welcome to TheJungle multiple times and note taking conducted for collecting and separating the data.Qualitative method is used for analysing the data. Purposive random sampling method is usedto choose the data based on its uniqueness between each data. The result of the study showsthat there several conversational implicature uttered by main characters in the movie. There isconnotative meaning in the uttered conversational implicature by main characters that can befound by understanding certain context, circumstances, each characters’ social life in themovie, and their personality as well.Keywords: implicature, conversational implicature, connotativeABSTRAKKomunikasi adalah sebuah kegiatan memberi dan menerima infomasi yang terjadi diantaradua orang atau lebih. Pada sebuah percakapan, banyak orang ingin menyampaikan informasilebih dari apa yang mereka ucapkan. Implikatur percakapan biasanya terjadi padapercakapan sehari-hari dan di dalam film. Penelitian ini membahas mengenai tipe-tipeimplikatur dalam percakapan menurut teori Grice (1975) dan mengenai makna konotatif dariimplikatur tersebut dengan menggunakan teori dari Leech (1983). Metode untukmengumpulkan data yang digunakan dengan mencatat. Data-data dari film tersebut diamatidengan cara menonton film berjudul Jumanji: Welcome to The Jungle secara berulang-ulangdan data-data tersebut dikumpulkan dan dipisahkan sesuai tipe implikatur percakapan olehGrice (1975). Metode kualitatif digunakan untuk menganalisis data-data tersebut. Metodesampel penelitian digunakan untuk memilih data berdasarkan keunikan data tersebut diantaradata-data yang lain. Hasil dari penelitian ini menunjukan bahwa ada beberapa implikaturpercakapan yang diucapkan oleh pemeran-pemeran utama. Makna konotatif juga dapatditemukan dalam implikatur percakapan dengan memahami konteks-konteks tertentu,keadaan, latar belakang dan kepribadian karakter utama.Kata Kunci: implikatur, implikatur percakapan, konotatif